Hepatic Alveolar Echinococcosis - Bresson-Hadni, Solange; Spahr, Laurent; Chappuis, François (Seminars in Liver Disease, 2021)
Hepatic alveolar echinococcosis (HAE) is a rare but severe zoonosis caused by the pseudotumoral intrahepatic development of the larval stage of the tapeworm Echinococcus multilocularis. HAE is present only in the Northern Hemisphere, predominantly in China. Currently, there is a significant resurgence of cases in historically endemic areas associated with emergence of HAE in countries not previously concerned. Today, in European countries, HAE is often discovered by chance; however, clinicians should be made aware of opportunistic infections that progressively emerged recently as a result of therapeutic or pathological immunosuppression. Ultrasonography is the key first-line diagnostic procedure, with specific serology providing confirmation in 95% of the cases. Albendazole, only parasitostatic, is the mainstay for treatment. Surgical resection, if feasible, is the gold standard for treatment, and more patients are currently eligible for this option because of an earlier diagnosis. The prognosis has considerably improved but remains poor in countries where access to care is less favorable.
Keywords: Echinococcus multilocularis; alveolar echinococcosis; liver surgery; instrumental procedures; albendazole